Unwilling or Unable? : Spatial, Institutional and Socio-Economic Restrictions on Females' Labor Market Access - Maarten van Ham; Felix Büchel (Institute for the Study of Labor (IZA), 2004)
We analyze the effects of regional structures on both females? willingness to work and the probability of being employed for those willing to work. Special permission was granted to link regional data to individual respondents in the German Socio-Economic Panel (GSOEP). Results of a bivariate probit model correcting for sample selection show that high regional unemployment discourages women from entering the labor market. Those who are willing to work find it easier to do so if living in regions with low regional unemployment rates, short distances to the next agglomeration, and – for mothers – a high density of childcare provision.
Keywords: J13; R23; J64; J21; 330; female labor supply; regional labor markets; childcare provision; bivariate probit model; Germany; Frauenerwerbstätigkeit; Arbeitsangebot; Regionale Arbeitslosigkeit; Regionaler Arbeitsmarkt; Kinderbetreuung; Schätzung; Deutschland